Understanding the processing-structure-performance relationship of graphene and its variants as anode material for Li-ion batteries: A critical review. (January 2020) - Sonia, Farjana J.; Aslam, M.; Mukhopadhyay, Amartya
Abstract: Graphenic carbon, as the lower (or nano-) dimensional form of graphitic carbon, is expected to allow lithiation/delithiation of an electrode constituted by the same in lesser time and possess greater specific gravimetric Li-storage capacity, as compared to graphitic carbon. The aforementioned positive aspects of graphenic carbon are expected/predicted/observed primarily due to the lower dimensional scale, greater specific surface area (SSA) and presence of 'defect' sites. Nevertheless, the types and extents of defects cast significant influences (both, positive and negative) on the Li-storage behavior/performance. For example, lack of ordering between constituent graphene layers suppresses Li-storage in the inter-layer spaces. Furthermore, despite providing additional sites for Li-storage, the defect sites themselves, in addition to enhanced SSA, cause irreversible Li-loss, voltage hysteresis, altering of the nature of potential profile from being flatter (restricted to lower potentials) to sloping from higher potentials, and also negatively affect the thermal stability/safety aspects. The concerned structural features of graphenic carbon, in turn, depend on the preparation route/condition. Not surprisingly, the associated literature base presents different viewpoints. In these contexts, the present review article looks into the correlations between preparation routes/conditions, structural features of graphenic carbon and electrochemical Li-storage behavior/performance; more from a fundamental perspective. Graphical abstract: Image 1